Perilaku Memilih Masyarakat pada Pilkada Kabupaten Sidoarjo Tahun 2020 - Ayu Amanda A'isyatul Khumairo'; Muhammad Asfar (Universitas Airlangga, 2023)
This study generally aims to find out the voting bahavior in the Sidoarjo 2020 election. There are three independent variables (X); Party identification (X1), group ties (X2), and candidate competency (X3). Meanwhile, there is one dependent variable: Voting Behavior in the 2020 Sidoarjo election (Y). Using quantitative methods and is included in the explanatory research category, and based on three voting behavior theory: sociological approach (Columbia school, psychologica approach (Michigan school), and rational approach. There were 100 respondents spread across all districts (18 districts) in Sidoarjo. From the results of the research and statistical analysis carried out, it is known that three supporting party variables (X1), Group Association (X2), and Candidate Competency (X3) are related to Voting Behavior in the 2020 Sidoarjo election (Y). In addition, it is known that voters for candidate number one (BHS-Taufiq) are more likely to be driven by the candidate’s competency variable, while voters for candidate number two (Mudhlor-Subandi) are more driven by party giver variables and group ties.